Meningkatkan Kualitas Sumber Daya Manusia (SDM) melalui Pelatihan Produktivitas oleh Dinas Tenaga Kerja Mandailing Natal - Muhammad Arif; Aldi Fernando (LPPM IAI Nasional Laa Roiba Bogor, 2022)
Mandailing Natal Panyabungan Manpower Office. The main task of the Manpower Service is as a government agency in the field of manpower in its working area. The functions of the Manpower Office include formulating manpower policies, implementing manpower policies, labor administration, labor supervision, reporting and evaluating the workforce. Related to its duties and functions, the local Manpower Office has several licensing powers such as Permits to Employ Foreign Workers (IMTA), Operational Permits for Employment Service Providers/Labourers, Employment Cards and Permits, Work Permits, to Work Center Institution Permits (BLK). . For information on requirements for obtaining a permit from the Manpower Office, costs (if any) and others, you can ask directly at the office. The public can also contact the telephone contact of the Manpower Office for a quick response, or access the website of the Manpower Office for general information and news related to employment. This research technique involves using a qualitative approach. Keywords: Department of Manpower, Job Training Center (BLK), Human Resources